Homology modeling, virtual screening and dynamics study of proteins involved in Pebrine - Serine protease inhibitor 106 and spore wall protein 26. Issue 17 (21st November 2020) - U M, Shravan; Karunakar, Prashantha; Krishnamurthy, V.
Abstract: Pebrine is a microsporidian disease caused by Nosema bombycis in Bombyx mori (silk worm) which results in brown/black spots. The affected larvae either spin cocoons which are flimsy with low silk content or not spin a cocoon. It has been hypothesised that Serine Protease Inhibitor 106 (SPN106) is responsible for evasion of host immune system by inhibiting the melanization process in silkworms. Also, Spore Wall Protein 26 (SWP26) has been observed to bind with Ig- like protein Bombyx mori turtle-like protein (Bm-TLP) facilitating the attachment of the microsporidian to the host and contributing to infectivity. Till date, there is no crystal structure of the proteins SPN106, SWP26 and Bm-TLP available. In this study, we performed homology modeling of the three structures using Modeller v9.18 and the binding pockets were identified. Virtual screening was conducted using AutoDock Vina on a ligand library consisting of 28, 870 lead-like molecules. The protein stability, compactness, fluctuations and protein-ligand interactions were investigated through Molecular Dynamics (MD) simulations studies using Desmond Maestro 11.3 and a potential lead molecule was identified. Communicated by Ramaswamy H. Sarma